Poverty profile: The rural North and Northeast of Brazil - Sergei Suarez Dillon Soares; Laeticia Rodrigues de Souza; Wesley Vieira da Silva; Fernando Gaiger da Silveira; Áquila Campos (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
Fortunately, both poverty and extreme poverty have shown a significant decrease in Brazil. According to data from the National Household Sample Survey (Pesquisa Nacional por Amostra de Domicílios - PNAD), poverty dropped over 20 per cent between 2004 and 2013, to about 9 per cent of the Brazillian population. Extreme poverty fell from about 7 per cent to 4 per cent over the same period. Much of this decline was due to the expansion of the labour market and the significant increase in transfers to poor households, through both social security and the Bolsa Família programme (Rocha 2013). [...]
Keywords: 330; poverty profile; rural; North; Northeast; Brazil